State Feedback Containment Control Of Multi-Agents System With Lipschitz Nonlinearity - Mohd Isira, Ahmad Sadhiqin; Md Yusop, Azdiana; Hairi, Mohd Hendra; Abdul Mutalip, Zaiton; Sheikh Hanis, Siti Nurfarihah; Wong, Chunyan; Casuat, Cherry D. (Institute Of Advanced Engineering And Science (IAES), 2021)
This paper studies the containment control problem of the leader-follower configuration in a multi-agents system included with a type of nonlinearity such as Lipschitz concerning continuous-time and directed spanning forest communication network topology. A state feedback containment controller is designed and proposed with control theory and the Laplacian network structure, where it utilizes the relative information of each agent. The controller designed ensures that the followers are contained by the leaders that form the convex hull formation. For containment action, a minimum of one leader must have a direct communication trajectory to the followers. Lyapunov stability theory is used to provide stability conditions after analyzing the network structure. Finally, it has been shown from the simulation that the followers are contained successfully with the proposed controller.